Financial Literacy and Financial Management Proficiency In Micro, Small, and Medium Enterprises - Ardi Armen; Sulis Yulyani; Aretha Widi Ailani (International Forum of Researchers and Lecturers, 2023)
This qualitative study aims to investigate the level of financial literacy and management proficiency among Micro, Small, and Medium Enterprises (MSMEs). The research employs a descriptive qualitative research design to explore the perceptions and practices of MSME owners or managers regarding financial matters. A purposive sampling technique is utilized to select participants, focusing on MSMEs operating in diverse industries and geographical locations. Data analysis involves thematic analysis, enabling the identification of recurring themes and patterns in participants' responses. The findings of this study provide insights into the financial knowledge and skills of MSMEs, highlighting potential areas for improvement and intervention. Ultimately, this research contributes to the understanding of the financial behaviors and challenges faced by MSMEs, aiding policymakers and stakeholders in developing targeted support programs and initiatives.